Description of Protallagma hoffmanni sp. nov. from the Peruvian Andes (Odonata: Coenagrionidae), including description of its larva - Hunger, Holger; Schiel, Franz-Josef (Zootaxa, 2012)
A new species, Protallagma hoffmanni, is described, illustrated, and diagnosed based on a series of males, females, andlarvae collected at Laguna Querococha (male holotype: Ancash region, Peru, S 09° 43' 33.6" W 077° 19' 51.8", 3,980 m a.s.l., MHNL).